Efficacy and safety of TAS-116, an oral inhibitor of heat shock protein 90, in patients with metastatic or unresectable gastrointestinal stromal tumour refractory to imatinib, sunitinib and regorafenib: a phase II, single-arm trial. (November 2019) - Doi, Toshihiko; Kurokawa, Yukinori; Sawaki, Akira; Komatsu, Yoshito; Ozaka, Masato; Takahashi, Tsuyoshi; Naito, Yoichi; Ohkubo, Shuichi; Nishida, Toshirou
Abstract: Aim: We evaluated the efficacy and safety of TAS-116, a novel class of an orally active selective inhibitor of heat shock protein 90, in patients with advanced gastrointestinal stromal tumour (GIST) after failure of three or more lines of standard treatment with imatinib, sunitinib and regorafenib. Methods: In this single-arm phase II study, patients received 160 mg/day oral TAS-116 for five consecutive days, followed by a 2-day rest. The primary end-point was centrally assessed progression-free survival (PFS). The secondary end-points were objective response rate, disease control rate, overall survival (OS), metabolic response rate, safety, pharmacokinetics and pharmacogenomics. Results: Forty-one patients were enrolled in Japan, and 40 patients underwent efficacy and safety evaluation. At the cut-off date, the median PFS was 4.4 months (95% confidence interval [CI], 2.8–6.0) and 12-week progression-free rate was 73.4% (95% CI, 58.1–88.7). Thirty-four patients (85.0%) had stable disease for ≥ 6 weeks. The median OS was 11.5 months (95% CI, 7.0–not reached). All patients experienced at least one treatment-related adverse event (AE), including diarrhoea (80.0%), decreased appetite (45.0%) and increase in blood creatinine level (42.5%). Grade ≥3 AEs and treatment-related grade ≥3 AEs occurred in 23 (57.5%) and 21 (52.5%) patients, respectively. All AEs resolved after dose modification, and no TAS-116–related AEs led to treatment discontinuation. Conclusion: TAS-116 showed significant activity in advanced GIST refractory to standard treatment. Further development of TAS-116 is warranted. Trial registration: JapicCTI-163182. Highlights: TAS-116 is an orally available and highly selective heat shock protein 90 (HSP90) inhibitor. The progression-free survival was 4.4 months, whereas it could be 0.9 months or less with best supportive care from past P3 trial results. The adverse events of TAS-116 were considered manageable compared with other HSP90 inhibitors. TAS-116 showed clinically meaningful activity, regardless of primary and secondary mutations in KIT and PDGFRA . TAS-116 may represent a novel treatment option for heavily pretreated gastrointestinal stromal tumour.